Perceptions of personal agency within communities: Validation of a diagnostic instrument. Issue 3 (27th May 2022) - Borron, Abigail; Lamm, Kevan W.; Atkins, D. Keith
ABSTRACT: The uniqueness of communities precludes a homogenous approach to program design, delivery, and evaluation. To account for such uniqueness, such approaches should necessitate that program managers have a thorough understanding of the targeted participants or consumers. This understanding can be achieved by determining residents' perceived personal ability, or personal agency, to act and function within the community. This paper represents an effort to operationalize the various capitals that comprise the Community Capitals Framework, focusing on the analysis and validation of an empirical instrument designed to quantify and measure perceived personal agency. Specifically, the objectives of this study were to (1) establish the factor structure of an overall personal agency scale and its capital components, (2) determine if the proposed models adequately fit the collected data, and (3) validate the scales by analyzing internal structure and consistency. The findings indicate that this personal agency scale is a valid and reliable instrument for developing community profiles based on personal agency perceptions. In addition, to account for individuals' personal agency offers a significant contribution to potentially evaluating the social impact of community development efforts longitudinally.